FORMULASI STRATEGI BERSAING (STUDI KASUS PADA RUMAH MAKAN SINAR MUDA CABANG PANAM PEKANBARU) - Oktiandi, Almi; Sutrisna, Endang (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Thish research was conducted at Rumah Makan Sinar Muda Cabang Panam. This business is engaged in culinary Padang food. The purpose of this research is to formulate a competitive strategy formulation on Rumah Makan Sinar Muda Cabang Panam using SWOT analysis techniques. This research is a descriptive research with a qualitative approach, where in this study only uses key informants to get the information needed. The types of data sources used in this study are primary data, namely data obtained through direct interviews. From the results of the analysis it can be seen that there are several alternative strategies that can be used as a tool to win competition in the culinary business of Padang cuisine. One strategy that can be applied to the ST strategy is the strategy implemented based on the utilization of the strengths to minimize the threatsKeywords : Competitive Strategi, SWOT Analysis, Alternative Strategy